Cannabis and Endocrine system: A narrative review - Sharma, P.; Balhara, Y.P.S. (Journal of Psychiatrists' Association of Nepal, 2018)
Cannabis is one of the most abused substances worldwide. The active component of cannabis is THC which has multiple effects in the endocrine system in both animal models and humans. The interest of scientific community in endocrine effects of cannabis is recent. We present a narrative review of endocrine effects of cannabis in different organ system along with description of possible mechanism both in the animal models and as well as in humans. We also highlight the need of research in this area especially in the population of South East Asia.